Regulatory and financial burdens of EU legislation in four Member States – a comparative study. Vol. 4: Burdens arising from Art. 30 and 33 of the General Data Protection Regulation - Lukas Harta; Anja Hoffmann; Matthias Kullas; Andrea De Petris; Carole Bui; Caroline Leroy-Blanvillain; Corinne Thierache; Jan Tiessen; Michael Schaaf; Jan-Felix Czichon; Jessica Catalano; Sara Banfi; et al. (Foundation for Family Businesses, 2023)
The research project on the costs of bureaucracy extends to four volumes on four different regulations. Part four is dedicated to General Data Protection Regulation. Here the information required in four member countries of the EU was examined along with the economic costs to companies that result in practice. – – Das Forschungsprojekt "Bürokratiekosten" erstreckt sich über vier Bände zu vier verschiedenen Regulierungen. Teil 4 widmet sich der Datenschutzgrundverordnung. Hier wurden die erforderlichen Angaben in vier Mitgliedsländern der EU untersucht und die ökonomischen Kosten in der Unternehmenspraxis.
Keywords: 330